Granting Birthright Citizenship - A Door Opener for Immigrant Children's Educational Participation and Success - Christina Felfe; Judith Saurer (Center for Economic Studies and ifo Institute (CESifo), 2014)
Does granting birthright citizenship help immigrant children integrating in the host country's educational system? We address this question using a reform of the German naturalization law in 1999 that entitled children born after January 1, 2000 with birthright citizenship. We use a difference-in-difference design that compares children born shortly before and after the cut-off in years of policy change and years where no policy change took place. Our empirical analysis relies on administrative data from school entrance examinations and on the German Micro Census. We find positive effects on immigrant children's educational participation, both in non-mandatory preschool and upper secondary school. In addition, birthright citizenship enhances children s socio-behavioral development.
Keywords: I21; K37; 330